Mother’s Role in Minimizing Phubbing Potential in Early Childhood: A Social Pathology Perspective - Mahmuriati Mahmuriati; Nurul Khansa Fauziyah; Nurul Hikmah; Hartini Mudarsa; Desi Murni Lasari (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
A mother has a significant role in minimizing the adverse effects of smartphone usage for children, including the risk of Phubbing. Dependence on smartphones can make children lazier and not interested in physically interacting with their playmates. In fact, social beings must be able to interact and care about their environment. Phubbing in early childhood can occur if there is no parental role in controlling smartphone use.  This study focuses on the mother’s role in minimizing Phubbing behavior since early childhood. This is descriptive research with qualitative approach. This study uses a purposive sampling technique with the characteristics of mothers who have children aged 2-6 years who are lightly addicted to smartphone. This study found that the way mothers deal with smartphone addiction in early childhood are by; observing carefully the children's activities, teach a good habit, discipline practice, make good communication. Dependence on smartphones and phubbing behavior is one of the pathological behaviors, as one of the consequences of human maladjustment on modernization that occurs quickly. Therefore, a mother needs to control the use of smartphones for her children, so that the potential for phubbing in children can be minimized.